Editorial: Navigating the modern marketplace: Integrating faith, ethics, and behavior in the digital age - Hendryadi, Hendryadi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
A Note from the Editorial Team, We are pleased to present this diverse and thought-provoking edition of Serambi Journal (Volume 2, Number 3, 2024). This issue serves as a critical lens through which we examine the complex intersection of contemporary professional life, technological disruption, and enduring Islamic principles. The collected research does not merely observe trends; it actively seeks to reconcile the dynamics of the modern world with a value-based framework. The papers in this edition address a central, pressing question: How do we maintain our ethical and spiritual compass in a world of digital noise, competitive pressures, and evolving workplace paradigms? The answers, as our contributors demonstrate, lie in a thoughtful synthesis of faith and practice.